IVTA as Adjunctive Treatment to PRP and MPC for PDR and Macular Edema: A Meta-Analysis - Liu, Lei (Public Library of Science, 2012)
BACKGROUND: To quantify the effect of a combination treatment of intravitreal triamcinolone acetonide (IVTA) injection, panretinal photocoagulation (PRP), and macular photocoagulation (MPC) in patients with proliferative diabetic retinopathy (PDR) and diabetic macular edema (DME). METHODOLOGY/PRINCIPAL FINDINGS: We conducted a meta-analysis and searched for reports concerning IVTA injection combined with PRP for the treatment of PDR and DME using Medline, EMbase, Web of Science, the Cochrane Library, and Google according to Cochrane evaluation guidelines. The quality of the reports was evaluated using the Jadad score. Only four studies were ultimately included in this meta-analysis and the fixed-effects model was used. Treatment with IVTA injection combined with PRP and MPC significantly improved BCVA (p<0.001) from one to six months, compared with PRP and MPC alone. There was a statistically significant mean difference in central macular thickness (CMT), at the one-month follow-up (p<0.001). No evidence of publication bias was present. There was a low level of heterogeneity in this group of studies. CONCLUSIONS/SIGNIFICANCE: This meta-analysis indicates that IVTA injection combined with PRP and MPC results in an improvement of BCVA, and CMT reduction in patients with PDR and DME.